Invasion status and impact potential of Florida bass Micropterus floridanus in South Africa - Khosa, Dumisani (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2020)
In South Africa, the introduction of alien fishes was largely driven by the development of recreational fishing opportunities. Government-backed programmes resulted in the introduction of four Black Bass species: Micropterus salmoides, Micropterus dolomieu, Micropterus punctulatus and Micropterus floridanus. These species are regarded as the primary threat to native biota and there is an urgent need to assess their spread and impacts. This thesis focuses on: assessing the current distribution of all four Black Basses; using genetic techniques to establish the extent of hybridisation between M. salmoides and M. floridanus, and using functional responses to assess the impact potential of M. salmoides and M. floridanus under the context dependence of temperatures and habitat complexity. Maximum entropy modelling of habitat suitability for Black Bass highlighted that M. salmoides had broad climatic suitability across South Africa, while suitability for M. dolomieu and M. punctulatus was restricted to the Cape Fold Ecoregion. An extensive area-based invasion debt was observed for all Micropterus spp. To better understand the dynamics of hybridisation between M. salmoides and M. floridanus, 38 species-diagnostic single nucleotide polymorphism was used to screen Black Bass populations from the Breede River and Kowie River catchments. Micropterus salmoides alleles were more prevalent than M. floridanus in both the Breede River catchments (69.1% and 30.9%, respectively) and Kowie River catchments (63.3% and 36.7%, respectively). However, isolated populations found in dams (reservoirs) remained free from hybridisation. To compare resource utilisation (i.e. per capita effects) between M. salmoides and M. floridanus, two experimental chapters were designed. Chapter 4 focuses on how temperature mitigates per capita effects between the two Black Basses. There was a significant decrease in per capita effects for M. salmoides with increasing temperatures, while the converse was true for M. floridanus. Chapter 5 gives an account of the influence of habitat complexity on per capita effects. The results showed that habitat complexity did mitigate per capita effects, specifically on M. floridanus, which showed a significant drop in per capita effects; however, no significant difference was recorded for M. salmoides. In the two experimental chapters, M. floridanus exhibited a superior per capita effect compared to M. salmoides, implying higher predation impact on native biota.
Keywords: Micropterus floridanus; Florida largemouth bass -- South Africa; Black bass -- South Africa; Micropterus floridanus -- South Africa -- Habitat; Florida largemouth bass -- South Africa -- Habitat; Black bass -- South Africa -- Habitat; Introduced fishes -- Environmental aspects -- South Africa